AB0619 Autologous Non-Myeloablative Hematopoietic Stem Cell Transplantation for Systemic Sclerosis: The Benefit of Quantitative Chest-CT Analysis for Response of Lung Involvement and Comparison with Results of Pulmonary Function Tests and Clinical Tests. (15th July 2016) - Marius, M.S.; Xenitidis, T.; Koetter, I.; Konstantin, N.; Henes, J.; Kloth, C.
Abstract : Background: Lung disease represents the leading cause of mortality and morbidity in patients with systemic sclerosis (SSc). In patients with rapid progressive disease immunoreset by high-dose chemotherapy accompanied by autologous stem cell transplant (auto-SCT) represents a possible rescue. For accurate evaluation and monitoring of lung parenchymal changes in patients undergoing treatment for SSc, different modalities (clinical examination, respiratory functional tests) are used, but these are all prone to some inaccuracies. Quantitative-CT represents a novel, fully automated technique able to exactly quantify lung volume and changes in CT-attenuation of lung parenchyma induced by SSc. Parameters like high attenuation value (HAV) and mean lung density (MLD) as well as percentile ranges 200–300/and300–400 Hounsfield units (HU) reflect at best lung involvement with this disease. Objectives: The aim of this study was to evaluate the course of SSc-related pulmonary changes following high-dose therapy & auto-SCT using quantitative chest-CT analysis and compare its results with those of established clinical and pulmonary function tests. Methods: Non-enhanced chest-CT examinations were performed before, directly after (0.49±0.20y) and at mean 2.2±2.1y after auto-SCT in 26 patients with SSc that were enrolled between March 2001 and March 2015. Chest-CT quantitative analysis was performed using fully automated software calculating inspiratory total lung volumes (TLV), mean lung densit (MLD), high attenuation values (HAV) and their distribution in the lung core vs. peel. All patients underwent pulmonary functional tests. The course of cutaneous SSc was evaluated by modified Rodnan skin score (mRSS). Classification of response to auto-SCT was performed at mean 6mo after auto-SCT based on the course of forced vital capacity (FVC) into responders 10% increase or stabilisation of FVC and non-responders >10% decrease in FVC. Results: The FVC course at 6mo classified the patients into responders 20 (76.9%) and 6 (23.1%) non-responders. Correspondingly, FVC, forced expiratory volume in 1s (FEV1s), vital capacity (VC) as well as single-breath diffusion capacity for carbon monoxide (DLCOcSB ) significantly improved (p=0.03/0.001/0.001/0.013). Mean modified Rodnan skin score (mRSS) improved from 27.35±9.25 before to 10.81±8.64 after auto-SCT (p=0.003) in responders. In non-responders no statistically significant improvement were registered. At CTD, total lung volume increased (p=0.018) whereas MLD (p=0.026) and HAV decreased (p=0.020) after auto-SCT only in responders. Improvement of CTH-parameters was stronger in the lung peel reflecting the typical localisation of SSc-fibroalveolitis. Changes of mRSS 6 months after auto-SCT correlate significantly with those 24 months after transplantation (r=0.575; p=0.031). Percental changes in MLD correlated well with FEV1 (r=0.733; p=0.016) in responders. Conclusions: Quantitative-CT analysis of lung parenchymal attenuation and volume in SSc-patients presenting lung involvement is accurate, can be easily and quickly accomplished being less dependent on patient's compliance and results match those of pulmonary function and clinical tests. Disclosure of Interest: None declared